OPTIMIZING WORKING CAPITAL FOR IMPROVED FINANCIAL PERFORMANCE IN THE QUOTED CONSUMER GOODS SECTOR OF NIGERIA - Ogunsola , Adebowale; Ameerah Opeyemi , Gbadebo (Journal of Allied Research in Management and Entrepreneurship (JARME), 2023)
This study examines the impact of working capital management on the financial performance of the consumer goods sector in Nigeria. Working capital is a critical component for the growth and development of business organizations, as it ensures the availability of sufficient current assets to meet short-term obligations. Effective working capital management strikes a balance between profitability and liquidity, thereby influencing a firm's overall financial health. This research aims to identify the factors that influence working capital and determine the optimal level of working capital that can enhance business performance and reduce risk. The composition of working capital varies across organizations, with receivables playing a significant role in the service sector and inventory dominating in the non-service sector. Proper construction and management of current assets and liabilities yield numerous benefits for businesses, emphasizing the importance of working capital management. However, excessive current assets can impair profitability, while insufficient assets can lead to illiquidity and an inability to meet short-term obligations. Working capital management is an integral element of a business's overall strategy, enabling value creation and enhanced competitiveness. By maintaining efficient levels of current assets and liabilities, firms can ensure operational effectiveness. Nevertheless, despite the availability of resources, some firms outperform others, highlighting the importance of understanding the role of working capital management in driving financial performance. The Nigerian consumer goods sector has experienced the negative consequences of poor working capital management, including factory shutdowns and subsequent unemployment. This study addresses this issue by examining the relationship between working capital management and financial performance in the sector. By analyzing financial data and employing appropriate statistical techniques, the study aims to provide insights into the impact of working capital management on profitability, liquidity, and overall financial well-being.